Bilateral Permanent Childhood Hearing Loss and Health-Related Quality of Life in Adolescence - Stavros Petrou; Kamran Khan; Colin Kennedy (MDPI AG, 2021)
Little is known about the impact of bilateral permanent childhood hearing loss (PCHL) on health-related quality of life (HRQoL). The objective of this study was to describe preference-based and non-preference based HRQoL outcomes in adolescence, from both self and proxy perspectives, amongst participants of the Hearing Outcomes Project. The Health Utilities Index Marks II (HUI2) and III (HUI3) and the PedsQLTM Version 4.0 Generic Core Scales were used to measure HRQoL based on self and parent proxy reports in 114 adolescents aged 13-19 years, 76 with bilateral PCHL and 38 with normal hearing, recruited from a population sample that was followed up from birth to adolescence. Descriptive statistics and multivariable analyses were used to estimate the relationship between severity of PCHL and HRQoL outcomes. PCHL was associated with decrements in mean multi-attribute utility score that varied between 0.078 and 0.148 for the HUI2 (p = 0.001) and between 0.205 and 0.315 for the HUI3 (p < 0.001), dependent upon the national tariff set applied and respondent group. Multivariable analyses revealed that, after controlling for clinical and sociodemographic covariates, mean HUI3 multi-attribute utility scores were significantly lower in adolescents with moderately severe, severe and profound hearing loss than in adolescents with normal hearing. Significant differences in physical functioning, social functioning, psychosocial functioning and total PedsQLTM scores were only observed when assessments by parents were relied upon, but these dissipated in the multivariable analyses. Bilateral PCHL is associated with poorer HRQoL outcomes in adolescence. Further studies conducted are needed to understand the trajectory and underpinning mechanisms of HRQoL outcomes following PCHL.